Determinants Of Purchase Decisions: The Role of Brand Image and Price - Nurmahatma, M Nicho; Yuniarinto, Agung (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2025)
The fierce competition in Indonesia's culinary industry requires companies to understand the factors that determine consumer purchasing decisions in order to ensure business sustainability. This study aims to analyse the role of brand image and price as determinants of purchasing decisions. The research design used is explanatory research with a quantitative approach. The research subjects are consumers of McDonald's Watugong branch in Malang City, with a sample of 120 respondents selected using purposive sampling. Primary data were collected through questionnaires and analysed using multiple linear regression analysis. The results showed that the variables of brand image (t = 5.825; sig. = 0.000) and price (t = 3.488; sig. = 0.001) both had a positive and significant effect on purchasing decisions. The coefficient of determination analysis shows that the two independent variables are able to explain 68.9% of the variation in the purchase decision variable, while the rest is influenced by other factors. It was also found that brand image has a more dominant influence than price. The implication of this study is to provide strategic input for management to continue strengthening brand image while maintaining a competitive pricing strategy. Theoretically, this study enriches the consumer behaviour literature by providing empirical evidence of the important role of brand image and price in the context of the fast food industry in Indonesia.